SUMO and SUMOylation Pathway at the Forefront of Host Immune Response - K., Sajeev T.; Joshi, Garima; Arya, Pooja; Mahajan, Vibhuti; Chaturvedi, Akanksha; Mishra, Ram Kumar (Frontiers in Cell and Developmental Biology, 2021)
Pathogens pose a continuous challenge for the survival of the host species. In response to the pathogens, the host immune system mounts orchestrated defense responses initiating various mechanisms both at the cellular and molecular levels, including multiple post-translational modifications leading to the initiation of signaling pathways. The network of such pathways results in the recruitment of various innate immune components and cells at the site of infection and activation of the adaptive immune cells, which work in synergy to combat the pathogens. Ubiquitination is one of the most commonly used post-translational modifications by all host cells for both temporal and spatial regulation of immune response pathways. Over the last decade, ubiquitin family proteins, particularly small ubiquitin-related modifiers (SUMO), have been widely implicated in host immune response. SUMOs are Ubiquitin-like (Ubl) proteins that are transiently conjugated to a wide variety of proteins through SUMOylation. SUMOs primarily exert their effect on target proteins by covalently modifying them. However, the non-covalent interaction between SUMO and the SUMO-interacting motif (SIM) in target proteins is also crucial. Unlike Ubiquitination, SUMOylation alters localization, interactions, functions or stability of target proteins. This review provides an overview of SUMO and immune pathways in general and then a detailed account of the regulation exerted by SUMO interactions and modifications of target proteins. Besides, a detailed account of the engagement of adaptor proteins, signalling molecules, transcriptional regulators, host immune factors, and pathogen proteins with SUMO pathway enzymes are utilized by the host immune system to mount a strong defense against the pathogenic infection. We also discuss the pathogen's ability to target the host SUMOylation pathway to infect the host and sustain the pathogenesis.